TRANSFORMING TULANG BAWANG MPP SERVICES THROUGH CHANGE MODELS AND BUSINESS PROCESS REDESIGN - Fera Seftinda; Novita Tresiana; Feni Rosalia (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2026)
The operation of Public Service Mall (MPP) in Indonesia is frequently constrained by service fragmentation, ego-sectarianism, and unaligned business processes, despite integrating various agencies into a single location. This study aims to construct a business process redesign mechanism as an instrument to strengthen service quality at the Tulang Bawang Regency MPP. A qualitative approach with an explanative single-case study design was employed, utilizing in-depth interviews, observations, and documentation. The results indicate that service transformation does not occur linearly but through a mixed governance mechanism that combines formal procedures with adaptive, informal coordination among actors in the field. Service digitalization serves as the primary driving factor forcing organizations to implement an Emprical Model of Business Process Redesign Mechanisms. This model consists of seven circular stages: initial condition, triggers, drivers, socio-technical systems, change mechanisms, business process redesign, and optimization outcomes. In conclusion, public service optimization is not merely a technical-digital intervention. Instead, its is the product of a harmounious interaction between actor capacity, institutional legitimacy, and adaptive technological systems to ensure sustainable governance.